Roadheader positioning method combining total station and strapdown inertial navigation system - ZHANG Xuhui; LIU Boxing; ZHANG Chao; YANG Wenjuan; ZHAO Jianxun (Gong-kuang zidonghua, 2020)
In order to solve the problems that roadheader positioning method based on total station could not locate because light path could be blocked due to excessive dust in coal mine underground and cumulative error of the method based on strapdown inertial navigation system(SINS) increased gradually with time, a roadheader positioning method combining total station and SINS was proposed. Firstly, total station is used to measure position parameters of roadheader, and SINS is used to measure and calculate position and posture parameters. Then, longitude and latitude of roadheader position measured by SINS are converted into coordinate values under Xi'an 80 coordinate system, so as to realize unification with total station measurement coordinate system. Finally, Kalman filtering method is used to fuse measured data of total station and SINS, so as to obtain position and attitude data of roadheader. The experimental results show that the method has high poisoning precision: in x direction, the maximum positioning error is 0.029 1 m, the minimum error is 0.010 0 m, and the average error is 0.019 93 m; in y direction, the maximum positioning error is 0.029 5 m, the minimum error is 0.011 0 m, and the average error is 0.018 26 m.